Development of Speaking Skills through Cooperative Learning - Urbánková, Kateřina (Univerzita Pardubice, 2023)
The bachelor thesis deals with cooperative learning and its use for the development of speaking during English classes. The work aims to investigate whether and how teachers use the principles of cooperative learning to develop speaking during English classes at a lower secondary school. First, communication competence and speaking as a language skill are introduced. Further, cooperative learning is discussed, emphasising cooperation between students, thereby creating the conditions for language learning. The paper is divided into two parts - theoretical and practical. The theoretical part forms the basis for the research described in the practical part.
Rozvoj řečové dovednosti mluvení prostřednictvím kooperativního vyučování
Keywords: komunikační kompetence; mluvení; kooperativní učení; principy kooperativního učení; spolupráce; communicative competence; speaking; cooperative learning; principles of cooperative learning; cooperation